Axial compressive behavior and modeling of fiber-reinforced polymer-concrete-steel double-skin tubular stub columns with a rectangular outer tube and an elliptical inner tube. (1st June 2022) - Wang, Yanlei; Zhong, Yang; Wan, Baolin; Zhang, Bing; Wei, Zitao; Bai, Yulei
Highlights: Rectangular FRP-concrete-steel double-skin tubular columns (DSTCs) are tested. Four parameters are considered to study the axial compressive behavior of DSTCs. The axial stress-strain curves of confined concrete are approximately trilinear. Increasing aspect ratio has positive effect on the behavior of confined concrete. A design-oriented three-stage stress-strain model of rectangular DSTCs is proposed. Abstract: This paper presents the experimental results of monotonic axial compression tests on eighteen glass fiber-reinforced polymer (FRP)-concrete-steel double-skin tubular stub columns (DSTCs) with a rectangular outer glass FRP tube and an elliptical/rectangular inner steel tube, as well as eight rectangular glass FRP-confined hollow stub columns (FCHCs) with an elliptical inner void. The effects of cross-sectional aspect ratio, FRP thickness, void area ratio and the shape of inner steel tube (i.e., elliptical and rectangular) on the axial compressive behavior of confined concrete core in rectangular DSTCs are considered and analyzed. The test results demonstrate that rectangular DSTCs possess excellent bearing capacity and ductility. Additionally, the axial stress-strain curves of confined concrete core in rectangular DSTCs are approximately trilinear and show obvious post-peak softening phenomenon because of the non-uniform and insufficient confinement. Furthermore, the larger aspect ratio, the thicker FRP tube, the higher void area ratio, as well as elliptical inner steel tube (compared with rectangular) have positive confinement effect on the axial compressive behavior of confined concrete core in rectangular DSTCs. Based on the analysis of experimental data, a design-oriented three-stage stress-strain model (considering post-peak softening behavior) of confined concrete in rectangular DSTCs with elliptical inner steel tube is proposed. Through the comparison, it is found that the predictions calculated by the proposed model accord well with the experimental results.